Studies of History, Language and Culture of Yukaghirs of Yakutia in 1960-1980-ies - A. A. Suleymanov (Научный диалог, 2018)
On the basis of the analysis of scientific literature and complex of archival material, including those introduced by the author into scientific circulation for the first time, the author presents a pioneer in the domestic historiography attempt of scientific understanding of the history of research activities relating to various aspects of the life of the Yukaghirs of Yakutia in the period from the end of the fundamental Yukaghir complex expedition to the beginning of a new stage in the development of the domestic Yukaghir studies and Russian science in general. In this regard, the main research initiatives implemented in the specified chronological framework are identified and considered. Their personal structure, a technique of carrying out, geography and the main directions are shown. The analysis of the key propositions developed by the participants of these initiatives was carried out. It is established that an important place in the work of scientists during the period under review took the understanding of the materials obtained during the Yukaghir complex expedition, as well as the accumulation of new information, also in the course of research, which included fundamentally new areas of research for Yukaghir studies. It is noted that thanks to the work done, scientists were able to obtain data characterizing the ethnic history, genetic relations and development of the Yukaghir language, language and ethno-social processes taking place in their environment.